Suco de caju contendo oligossacarídeos prébioticos - Silva, Isabel Moreira da (2010)
Functional foods are now a research priority due to growing demand for foods that, besides the basic function of nurture, can bring benefits. Thus, studies for the development of prebiotics become interesting. The enzyme dextransucrase in a medium containing sucrose and an acceptor as substract synthesizes prebiotics oligosaccharides. The cashew apple juice works as a source of acceptors, since it is rich in glucose and fructose. The production of dextransucrase enzyme can be accomplished by fermentative process by inoculating the bacterium Leuconostoc mesenteroides NRRL B512F into a culture medium containing sucrose.Thus the aim of this work was the production of prebiotic oligosaccharides by enzymatic process with addition of the dextransucrase enzyme to the clarified cashew apple juice. Based on the results we can conclude that the clarified cashew apple juice can be used as low cost alternative substrate for the synthesis of prebiotic oligosaccharides through enzyme synthesis using the dextransucrase enzyme. Dextran yeld was favored by the combination of low concentrations of sucrose and reducing sugars. The formation of oligosaccharides was favored by increasing the concentration of reducing sugars and by the combination of high concentrations of sucrose and reducing sugars, where the largest concentration of oligosaccharides obtained was 104.73 g/L using 75g/L sucrose in combination with 75g/L of reducing sugars and finally the qualitative analysis shows that at concentrations of 25 g/L and 75g/L sucrose and reducing sugar, respectively, is possible to obtain oligosaccharides of degree of polymerization up to 12.